A monetary policy rule for Russia, or is it rules? - Iikka Korhonen; Riikka Nuutilainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
We estimate several monetary policy rules for Russia for the period 2003–2015. We find that the traditional Taylor rule describes the conduct of monetary policy in Russia reasonably well, whether coefficients are restricted to being the same or allowed to change over the sample period. We find that the Bank of Russia often overshot its inflation target and that extensive overshooting is associated with large depreciations of the ruble, testifying to the importance of the exchange rate in the conduct of monetary policy in Russia.
URN:NBN:fi:bof-201602161029
Keywords: E31; E43; E52; P33; 330